Transcatheter aortic valve implantation in a patient with suspected hereditary von Willebrand disease and severe gastrointestinal bleeding – a case report. Issue 4 (November 2019) - Mirna, Moritz; Lichtenauer, Michael; Theurl, Thomas; Ausserwinkler, Mathias; Topf, Albert; Westphal, Theresa; Gampenrieder, Simon Peter; Pretsch, Ingrid; Greil, Richard; Hoppe, Uta C
Introduction: von Willebrand disease is the most common hereditary coagulopathy and is characterised by a deficiency in the quantity or quality of the von Willebrand factor. Heyde Syndrome, in contrast, is an acquired form of von Willebrand syndrome (AVWS) due to calcific aortic valve stenosis, characterised by gastrointestinal bleeding from angiodysplasia. Case presentation: A 73-year-old patient presented with severe gastrointestinal bleeding and stated that she suffered from hereditary von Willebrand disease. Upon echocardiography, a severe aortic valve stenosis was found, and hence the suspicion of additional AVWS was raised. Since endoscopic interventions and conservative therapeutic approaches did not result in a cessation of the bleeding, transcatheter aortic valve implantation (TAVI) was performed to stop the additional shear stress on von Willebrand factor. This resulted in cessation of the bleeding. Conclusion: Retrospectively, this life-threatening gastrointestinal bleeding was a result of severe Heyde Syndrome, which could be alleviated by TAVI. Whether the patient had suffered from inherited von Willebrand disease in the past, remains uncertain. AVWS should be considered in patients with suspected inherited von Willebrand disease and concomitant severe aortic valve stenosis, since it constitutes a treatable cause of a potentially severe bleeding disorder.